The Effectiveness of Uno Kimia Cards in Enhancing Understanding of Molecular Shape Topic Among High School Students - Ahmad*, Mujahidin; Erlina, Erlina; Lestari, Ira; Enawaty, Eny; Queiroz, Carla Cristina (Jurnal IPA & Pembelajaran IPA, 2025)
Understanding molecular shapes poses significant challenging for students due to the abstract nature of the topic, which can limit engagement and comprehension. This study aims to investigate the effectiveness of uno kimia (Umia) cards as an instructional tool to enhance students comprehension on students' understanding of the molecular shapes topic at SMA Negeri 1 Mentebah. The study used a quasi-experimental design with a nonrandomized control pre-test and post-test was utilized, involving sixty tenth-grade students divided into experimental group using Umia cards and control groups employing traditional teaching methods. Learning outcomes were assessed using validated pre-test and post-test instruments, with content validity index scores of 0.88 and 0.82 for the teaching module, both results confirming the instruments were valid. The chi-square test revealed no significant difference in the control group (p = 0.504), while the experimental group using Umia cards showed significant improvement (p = 0.007). A non-parametric Mann-Whitney U test indicated homogeneity between the groups (p = 0.982). Results showed significant improvement in the experimental group's understanding, with an 88% increase, a high effect size (Cohen's d = 1.259), and a high N-gain score (mean = 0.7106) compared to the control group (mean = 0.4103). The findings indicate that the Umia cards are a highly effective pedagogical tool, capable of improving both student engagement and conceptual understanding in molecular shape topic. These results underscore the potential of interactive learning media in addressing challenges associated